tRNA engineering strategies for genetic code expansion - Kim, YouJin; Cho, Suho; Kim, Joo-Chan; Park, Hee-Sung (Frontiers in Genetics, 2024)
The advancement of genetic code expansion (GCE) technology is attributed to the establishment of specific aminoacyl-tRNA synthetase/tRNA pairs. While earlier improvements mainly focused on aminoacyl-tRNA synthetases, recent studies have highlighted the importance of optimizing tRNA sequences to enhance both unnatural amino acid incorporation efficiency and orthogonality. Given the crucial role of tRNAs in the translation process and their substantial impact on overall GCE efficiency, ongoing efforts are dedicated to the development of tRNA engineering techniques. This review explores diverse tRNA engineering approaches and provides illustrative examples in the context of GCE, offering insights into the user-friendly implementation of GCE technology.